An Analytical Study of COVID-19 Impacts on Consumer Buying Behaviors for FMCG products in India - Sekhara, Soma (Nepalese Journal of Management Science and Research, 2023)
The aim of article is to identify and analyze all the impacts of COVID-19 on consumer buying behavior for Fast Moving Consumer Goods in India and significant changes that takes place post-covid-19. The awareness and understanding of changing consumer behavior can help brand marketers future-proof their operations in the post COVID period. The current situation currently prevailing in global markets is mainly influenced by external factors- the COVID-19 pandemic and the effects of political and governmental steps and the economic situation. This paper mainly aims to identify changes in consumer behavior when buying basic products - food, clothing drugstore goods, and footwear and electronics during the pandemic of COVID-19.